ICAO AVIATION OCCURRENCE CATEGORIES SIGNIFICANTLY AFFECTING AVIATION SAFETY IN POLAND FROM 2008 TO 2015 - Paweł GŁOWACKI; Włodzimierz BALICKI (Scientific Journal of Silesian University of Technology. Series Transport)
Poland, as a member of the EU, is represented within the ICAO, by the European Aviation Safety Agency. However, this does not relieve our country from the responsibility of developing a state safety programme (SSP). The need to set up such a programme, which has to be specific to every country involved in aviation operation, was introduced by the ICAO’s Annex 19. One of the important points in Annex 19 is: “5.2.1 Each State shall establish and maintain a safety database to facilitate the effective analysis of information on actual or potential safety deficiencies obtained, including that from its incident reporting systems, and to determine any actions required for the enhancement of safety”. The Polish Civil Aviation Authority, along with other databases, manages the European Coordination Centre for Aviation Incident Reporting Systems (ECCAIRS). The authors (who are specialists dealing with exploitation processes in aviation) have conducted a laborious processing of the data contained in the ECCAIRS database, analysing them based on various criteria: aviation occurrence categories (as defined by the ICAO), phases of flight for different airports in Poland etc. Aircraft with an maximum take-off mass (MTOM) <5,700 kg (mainly general aviation) and for aircraft with an MTOM >5,700 kg (commercial aviation) were considered separately. It was found that the most events are those that relate to power plant (SCF-PP) airframes and related system (SCF-NP) failures, followed by collisions with birds (BIRD), events related to airports (ADRM) and events related to the required separation of aircraft (MAC). For lighter aircraft, the dominant categories are ARC, CTOL, GTOW and LOC-I events. The article presents a proposed method for predicting the number of events, determining the alert levels for the next years and assuming a normal distribution (Gaussian). It is one of the first attempts to use actual data contained in the database of events on airports in Poland. The results of this analysis may support the decisions of supervisory authorities in the areas where security threats are most important.